Bisnis Warung Tenda Berkelanjutan: Pengolahan Limbah Minyak Goreng pada Paguyuban Pecel Lele Lamongan Desa Maduran - Marista Winanti Sutadipraja; Eka Desiyanti; Maria Dewi (Jurnal Pengabdian Pada Masyarakat, 2021)
SUSTAINABLE RESTAURANT BUSINESS. PROCESSING OF COOKING OIL WASTE AT THE LAMONGAN PECEL LELE SOCIAL GROUP, MADURAN VILLAGE. In contrast to traditional business activities that are only centered on profit, sustainable businesses think about environmental and social impacts. Lamongan Pecel Lele Restaurant is often found in almost every region in Indonesia. The most waste generated from these business activities is cooking oil or commonly called used cooking oil. Waste used cooking oil if not treated properly will have a negative impact on health and the environment. One of the target goals number 12 of the SDGs is to achieve environmentally friendly management of chemicals and other wastes throughout their life cycle, in accordance with an agreed international framework, and significantly reduce the release of these materials into air, water and soil in order to minimize impacts bad material for human health and the environment. Seeing this phenomenon, the Ahmad Dahlan Jakarta Institute of Technology and Business felt the need to provide community service with the theme "Sustainable Restaurant Business. Processing of Cooking Oil Waste at the Lamongan Pecel Lele Paguyuban, Maduran Village ". Community service activities include extension activities, provision of manuals and tutorial videos, provision of tools and materials for soap making. The results felt by the service partners producing used cooking oil soap within one month after processing it is used independently for each member as hand washing soap at service partner restaurants, cleaning clothes, or cleaning restaurant floors.